Analysis Financial Performance at PT. Bank Sulselbar Period 2017-2021 - We Batary Pada; M. Ilham Wardhana Haeruddin; Nurman; Anwar Ramli; Uhud Darmawan Natsir (Economics and Business Journal (ECBIS), 2023)
This study aims to determine the financial performance of PT. Bank Sulsebar for the 2017-2021 period is based on three types of ratios, namely liquidity ratios, solvency ratios and profitability ratios. The population in this study is the financial statements of PT. Sulselbar Bank. The sample in this study is the financial statements of PT. Bank Sulselbar Period 2017-2021. The data collection technique used is documentation. The data analysis technique used is descriptive quantitative method and financial ratio analysis. The results of this study indicate that the calculation of the ratio of liquidity and profitability ratios of PT. Bank Sulselbar is above the standard of the banking industry. Calculation of the solvency ratio of PT. Bank Sulselbar is below the standard of the banking industry. So it can be concluded that the financial performance of PT